A New Spectrophotometric Determination of Vanadium (V) in Pharmaceutical and Steel Samples - Siva Rama Sharma, B.; Syama Sundar, B. (Asian Journal of Chemistry, 2010)
Vanadium(V) is quantitatively extracted into nitrobenzene as a ternary complex in the presence of 8-hydroxyquinoline (HR) and chlorosubstituted acetic acids, namely monochloroacetic acid (MCA), dichloroaceticacid (DCA) and trichloroacetic acid (TCA). The optimum experimental conditions for the quantitative recovery of vanadium and also the composition of the extracted ternary species have been determined. The effectiveness of these chlorosubstituted acetic acids as synergists for the extraction of vanadium is found to have the order TCA > DCA > MCA. A sensitive analytical procedure for vanadium is developed based on the formation of the ternary complex with HR and TCA which is highly suitable for its determination in pharmaceutical and standard steel samples.